The Implementation Of Moral Values In Surah Al-Hujurat Verses 11-13 As The Basis For “Stop Bullying” Habituation At MI Baitur Rohman Asemrowo Surabaya - Wila, Wilayatul Istianah, S.H. (Journal of Teacher Training and Educational Research, 2025)
Bullying is a social problem that often occurs in educational settings and can have a negative impact on students' psychological development. In Islam, the moral values contained in the Qur'an can be used as guidelines to shape the character of students to get used to behaving well and avoiding actions that harm others. This study aims to examine the implementation of moral values in Surah Al-Hujurat verses 11-13 as the basis for habituation "Stop Bullying" at MI Baitur Rohman Asemrowo Surabaya. The method used in this research is a qualitative approach with data collection techniques through observation, interviews, and documentation. The results showed that the moral values in the verse, such as the prohibition of demeaning others, reproaching, calling bad names, prejudice, and backbiting, have been implemented through habituation activities which include Islamic value-based learning, teacher exemplary, and special anti-bullying programs at school. The implementation of these values has proven effective in shaping students' awareness to respect each other and maintain ukhuwah Islamiyah in the school environment. Thus, strengthening moral values in the Qur'an is an important strategy in instilling anti-bullying character in education.